2021
DOI: 10.1016/j.ecolecon.2021.106946
|View full text |Cite
|
Sign up to set email alerts
|

Do farmers prefer increasing, decreasing, or stable payments in Agri-environmental schemes?

Abstract: Nearly all Agri-Environmental Schemes (AES) offer stable annual payments over the duration of the contract. Yet AES are often intended to be a transition tool, designed to trigger changes in farming practices rather than to support them indefinitely. A decreasing sequence of payments thus appears particularly attractive as a reward structure for AES. The standard discounted utility model supports this notion by predicting that individuals should prefer a decreasing sequence of payments if the total sum of outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Choice experiments (CE) is an effective tool for analyzing farmers’ preferences, and many scholars have applied choice experiments to areas related to ecological compensation [ 37 , 38 , 39 , 40 , 41 ]. The CE method provides estimation to more information and enables simultaneous analysis of farmers’ preferences for policy packages [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Choice experiments (CE) is an effective tool for analyzing farmers’ preferences, and many scholars have applied choice experiments to areas related to ecological compensation [ 37 , 38 , 39 , 40 , 41 ]. The CE method provides estimation to more information and enables simultaneous analysis of farmers’ preferences for policy packages [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Central Statistics Agency noted a decrease in the number of farmers, wherein 2018 the number of farmers as many as 35.70 million, in 2019 as many as 34.58 million, in 2020 as many as 33.4 million. Land limitations also prevent youth from working in the agricultural sector [8]. Channels and content have not been utilized to the fullest to increase youth knowledge and interest in the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
“…Channels and content have not been utilized to the fullest to increase youth knowledge and interest in the agricultural sector. Youth perception and interest in agriculture are obstacles [8]. Deficient awareness of youth in the agricultural sector, even Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi) Vol.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established in this literature that contract attributes influence farmers' acceptance decisions (e.g. Bougherara et al, 2021;Christensen et al, 2011;Santos et al, 2016). Beyond the contract itself, previous research has shown that participation in AES is also related to farmer and farm characteristics (e.g.…”
Section: Contract Farming and The Adoption Of Si Practicesmentioning
confidence: 99%
“…Further, only Ricome et al (2016) and Banterle and Stranieri (2013) have focussed on the European context from a value chain perspective, while the majority of studies assessing (potential) adoption of sustainable practices in Europe usually consider government-led agri-environmental schemes (AES) (e.g. Bougherara et al, 2021;Kuhfuss & Subervie, 2018;Santos et al, 2016). Value chain and commercial private sector initiatives, such as CF, have found only limited space in the literature on adoption of sustainable practices, against the evidence that private actors play a significant role, e.g.…”
Section: Introductionmentioning
confidence: 99%